Transmission of porcine circovirus 2 (PCV2) by semen and viral distribution in different piglet tissues - Gava D.* (2008)
Porcine circovirus infections are caused by the porcine circovirus 2 (PCV2). Among six different clinical manifestations involving respiratory, enteric, nervous and reproductive signs, the postweaning multisystemic wasting syndrome (PMWS) is the most important and studied disease. However, reproductive failures associated with PCV2 have been increasingly reported. Some studies have shown the possible contamination of sows by semen of PCV2 positive boars. In order to investigate the transmission of PCV2 by contaminated semen and its ability to infect the sow and piglets, 20 PCV2 negative sows were inseminated, 10 with negative boar semen and 10 with previously nested-PCR tested positive boar semen. The sows were weekly monitored and blood samples were collected. Based on the results, 4 out 20 sows were selected (1 sow was PCR negative and inseminated with a negative semen, 2 sows were PCR negative and inseminated with a positive semen and 1 sow was PCR negative and inseminated with a positive semen, but became PCR positive around the 30 days of pregnancy). After weaning, 12 male piglets, 3 of each sow, were selected and maintained under isolation. In order to investigate which organs harbored the virus, the young pigs were necropsied around 9 months of age. Samples of serum collected monthly were tested by immunocitochemistry (ICC), and all 12 pigs serum converted. Samples of lymphoid, systemic and reproductive organs were analyzed by nested-PCR and immunohistochemistry (IHC). Evaluation of the samples by nested-PCR, revealed that several tissues were positive in 10 of 12 pigs, mainly the lymph nodes, bone marrow and spleen. Various samples were positive by IHC in 8 of 12 piglets, being the lymph nodes, tonsils and bulbourethral glands the most frequently positive. Thus, the results of testing different samples, in the 3 tests (ICC, nested-PCR and IHC) were complementary. These results show that PCV2 transmission through semen to the sows and piglets may occur and may also represent a potential risk for the herd.